Optimising low molecular weight hydrogels for automated 3D printing. Issue 45 (30th October 2017) - Nolan, Michael C.; Fuentes Caparrós, Ana M.; Dietrich, Bart; Barrow, Michael; Cross, Emily R.; Bleuel, Markus; King, Stephen M.; Adams, Dave J.
Abstract : We demonstrate the optimised 3D printing of low molecular weight gels. Abstract : Hydrogels prepared from low molecular weight gelators (LMWGs) are formed as a result of hierarchical intermolecular interactions between gelators to form fibres, and then further interactions between the self-assembled fibres via physical entanglements, as well as potential branching points. These interactions can allow hydrogels to recover quickly after a high shear rate has been applied. There are currently limited design rules describing which types of morphology or rheological properties are required for a LMWG hydrogel to be used as an effective, printable gel. By preparing hydrogels with different types of fibrous network structures, we have been able to understand in more detail the morphological type which gives rise to a 3D-printable hydrogel using a range of techniques, including rheology, small angle scattering and microscopy.